Is weekend effects a myth? - Maria Marcellinda Stevie; Said Kelana Asnawi (Jurnal Ekonomi Perusahaan, 2021)
In the widely recognized phenomenon of the weekend effect, it is commonly believed that Monday's stock prices are lower than Friday's. The authors believe that stock movements are unique in each country and sector. Does this phenomenon also occur sectorally in Indonesia? This study intends to answer this question. Therefore, the authors study the differences in stocks on Friday and Monday in the consumer, and property, agriculture sectors on the Indonesian Stock Exchange (IDX). The research problem is there a difference in stock prices and returns on Friday and Monday? To answer this question, the authors chose the sample purposively. The data are the open-close and trading volume of the three selected sectors on the IDX in the period January 2018 to September 2020. Using the independent sample t-test as an analytical tool, the study shows no difference between return and trading volume on Friday and Monday. Thus, the agriculture, consumer, and property sectors in Indonesia, experience no market anomaly called the weekend effect. Original Article | Turnitin